ASEAN as an actor in international fora : reality, potential and constraints - Nguitragool, Paruedee; Ruland, Jurgen, 1953- (Cambridge : Cambridge University Press, 2015)
'ASEAN as an Actor in International Fora addresses a blind spot in ASEAN research and in comparative regionalism studies by assessing why, how, when and to what extent ASEAN member governments achieve a collective presence in global forums. Written for academic researchers and practitioners working in areas such as international relations, political science and international law, it examines ASEAN's negotiating behavior with a novel four-point cohesion typology. The authors argue that ASEAN's'cognitive prior' and its repository of cooperation norms have affected ASEAN's negotiation capacities, formats, strategies and cohesion in international forums. Using two case studies - one on ASEAN's cohesion in the WTO agricultural negotiations and one on UN negotiations on forced labor in Myanmar - they examine ASEAN's collective actions at different stages of negotiation, in different issue areas and in different negotiating forums. The book concludes by providing recommendations for strengthening ASEAN's international negotiation capacities'--
'This book comprising the ten member states of Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand and Viet Nam, has undertaken intensified integration into the ASEAN Community through the Rule of Law and Institutions in its 2007 Charter'--
Keywords: ASEAN; Negotiation -- Southeast Asia; Regionalism -- Southeast Asia; Southeast Asia -- Economic integration